EVALUATION OF CREATIVE ECONOMY REGULATION AND IMPLEMENTATION IN INDONESIA AND ITS RELATION TO ASEAN MEMBER STATES (AMS) IN ORDER TO EFFECTUATE CREATIVE ASEAN RELIABILITY - Adiastuti, Anugrah; Primasari, Lushiana (UI Scholars Hub, 2015)
Competitiveness in trade activity does get higher time after time. It can be seen from the powerful competitive products either from quantity or quality aspects. ASEAN as one kind of regionalism throughout the world has affected into international trade flows development. The sector that cannot be forsaken is culture industry and creative economy. Through creative economy development, it influences states economic transformation which is can be perceived from the upgrading state qualification, based on World Bank system, for instance Singapore and Malaysia. It becomes important due to the creative economy development is not only limited to trade in goods circulation but also happening on trade in services, intellectual property rights and investment. In accord with those circumstances, this research intends to evaluate the creative economy regulation and implementation in Indonesia and its relation to ASEAN Member States (AMS) either for people to people connectivity, physical connectivity, institutional connectivity and/or resources connectivity in order to be contemplated as standard regulation considerations of creative economy protection in ASEAN. Ultimately, based on this evaluation, it could achieve Creative ASEAN reliability for enhancing economic growth and income in ASEAN.